REKONSTRUKSI INTEGRALISTIK INSTRUMEN MATA UANG BERBASIS SYARIAH (DIGITAL GOLD CURRENCY) - Faisal, Agus; Wahid, Ahmad Nur; Yuliani, Irma (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Digital currency is the result of the evolution of the medium of exchange that continues to develop from time to time among the people. Changes in payment instruments from traditional systems to digital systems are expected to have a positive impact on payment traffic both in terms of speed, ease and security for the community. The DGC (Digital Gold Currency) study was explored in more depth using qualitative descriptive methods and the application of integralistic technology reconstruction. Narrative analysis starts from the study of the history of the development of currency types to the use of digital currencies, the advantages and benefits for the economy in general. Furthermore, the reconstruction of integralistic technology for the formation of DGC (Digital Gold Currency) was carried out by combining three concepts, including: first, the use of currency technology (digital money) can provide convenience and security for the community, second, the use of gold as a currency standard due to the stability of its value and its existence is universally recognized, Third, the application of Islamic values in the formation of currency (shari'ate money) by returning the function of money in accordance with Islamic sharia.